Intravenous IgM-enriched immunoglobulins in critical COVID-19: a multicentre propensity-weighted cohort study - Rahmel, Tim; Kraft, Felix; Haberl, Helge; Achtzehn, Ute; Brandenburger, Timo; Neb, Holger; Jarczak, Dominik; Dietrich, Maximilian; Magunia, Harry; Zimmer, Frieda; Basten, Jale; Landgraf, Claudia; et al. (Critical care, 2022)
BACKGROUND: A profound inflammation-mediated lung injury with long-term acute respiratory distress and high mortality is one of the major complications of critical COVID-19. Immunoglobulin M (IgM)-enriched immunoglobulins seem especially capable of mitigating the inflicted inflammatory harm. However, the efficacy of intravenous IgM-enriched preparations in critically ill patients with COVID-19 is largely unclear. - METHODS: In this retrospective multicentric cohort study, 316 patients with laboratory-confirmed critical COVID-19 were treated in ten German and Austrian ICUs between May 2020 and April 2021. The primary outcome was 30-day mortality. Analysis was performed by Cox regression models. Covariate adjustment was performed by propensity score weighting using machine learning-based SuperLearner to overcome the selection bias due to missing randomization. In addition, a subgroup analysis focusing on different treatment regimens and patient characteristics was performed. - RESULTS: Of the 316 ICU patients, 146 received IgM-enriched immunoglobulins and 170 cases did not, which served as controls. There was no survival difference between the two groups in terms of mortality at 30 days in the overall cohort (HRadj: 0.83; 95% CI: 0.55 to 1.25; p = 0.374). An improved 30-day survival in patients without mechanical ventilation at the time of the immunoglobulin treatment did not reach statistical significance (HRadj: 0.23; 95% CI: 0.05 to 1.08; p = 0.063). Also, no statistically significant difference was observed in the subgroup when a daily dose of ≥ 15 g and a duration of ≥ 3 days of IgM-enriched immunoglobulins were applied (HRadj: 0.65; 95% CI: 0.41 to 1.03; p = 0.068). - CONCLUSIONS: Although we cannot prove a statistically reliable effect of intravenous IgM-enriched immunoglobulins, the confidence intervals may suggest a clinically relevant effect in certain subgroups. Here, an early administration (i.e. in critically ill but not yet mechanically ventilated COVID-19 patients) and a dose of ≥ 15 g for at least 3 days may confer beneficial effects without concerning safety issues. However, these findings need to be validated in upcoming randomized clinical trials. Trial registration DRKS00025794 , German Clinical Trials Register, https://www.drks.de . Registered 6 July 2021.
Gesehen am 15.08.2022